Effects of oil pollution on the growth and rhizosphere microbial community of Calamagrostis epigejos - Ying Wei; Yukun Zhu; Liqun Yang; Chen Chen; Ming Yue; Zhuxin Mao; Yuchao Wang; Qian Li; Yang Li; Jinlin Lv; Wenyan Xue (Scientific Reports)
Abstract Bacteria, fungi, archaea, and viruses are reflective organisms that indicate soil health. Investigating the impact of crude oil pollution on the community structure and interactions among bacteria, fungi, archaea, and viruses in Calamagrostis epigejos soil can provide theoretical support for remediating crude oil pollution in Calamagrostis epigejos ecosystems. In this study, Calamagrostis epigejos was selected as the research subject and subjected to different levels of crude oil addition (0 kg/hm2, 10 kg/hm2, 40 kg/hm2). Metagenomic sequencing technology was employed to analyze the community structure and diversity of soil bacteria, fungi, archaea, and viruses. Additionally, molecular ecological network analysis was integrated to explore species interactions and ecosystem stability within these microbial communities. The functional profiles of soil microorganisms were elucidated based on data from the KEGG database. Results demonstrated a significant increase in petroleum hydrocarbon content, polyphenol oxidase activity, hydrogen peroxide enzyme activity, and acid phosphatase activity upon crude oil addition, while β-glucosidase content, fiber disaccharide hydrolase content, and tiller number decreased (P < 0.05). Proteobacteria and Actinobacteria were identified as dominant bacterial phyla; Ascomycota, Basidiomycota, and Mucoromycota were found to be dominant fungal phyla; Thaumarchaeota emerged as a dominant archaeal phylum; and Uroviricota represented a dominant viral phylum. The diversity of soil bacterial, fungal, archaeal, and viral communities increased with higher amounts of added crude oil. Ecological network analysis revealed a robust collaborative relationship among bacterial, fungal, archaeal, and viral community species in the control treatment (CK), while strong competitive relationships were observed among these species in the treatments with 10% (F10) and 40% (F40) crude oil concentrations. Structural equation modeling analysis indicated significant positive correlations between fungal community, viral community, enzyme activity, and plant growth; conversely, bacterial and archaeal communities showed significant negative correlations with plant growth (P < 0.05). Correlation analysis identified acid phosphatase as the primary environmental factor influencing soil microbial function. Acid phosphatase levels along with tiller number, aboveground biomass, and petroleum hydrocarbons significantly influenced the fungal community (P < 0.05), while underground biomass had a significant impact on the archaeal community (P < 0.05). Acid phosphatase levels along with cellulose-hydrolyzing enzymes, tiller number, and petroleum hydrocarbons exhibited significant effects on the viral community (P < 0.05). This study investigated variations in bacterial, fungal, archaeal, and viral communities under different crude oil concentrations as well as their driving factors, providing a theoretical foundation for evaluating Calamagrostis epigejos’ potential to remediate crude oil pollution.